1.12-W Q-switched Yb：KGW laser based on transmission-type Bi2Se3 saturable absorber - 刘京徽 田金荣 胡梦婷 徐润亲 窦志远 于振华 宋晏蓉 (中国物理B：英文版, 2015)
We present a passively Q-switched Yb：KGW laser based on a transmission-type saturable absorber of topological insulator：Bi2Se3.The saturable absorber is prepared on a 0.17-mm glass substrate and can translate intra-cavity for best performance nearly without influence on the laser mode.At a maximum pump power of 13.7 W,the central wavelength,pulse duration,repetition rate,and pulse energy of Q-switched pulse are 1043 nm,1.5 μs,175.4 kHz,6.39 μJ,respectively.The maximum output power is 1.12 W.To our knowledge,this is the highest average output power from passively Qswitched lasers with topological insulator saturable absorbers.